Using Pictionary as a Fun English Activity to Teach English at SMP IT Imam Syafii Cendikia Pekanbaru - Missi Tri Astuti; Diyah Ayu Riaziani; Octadino Haryadi; Fikri Nazif Hibatullah (Journal of Applied Linguistics, 2026)
English has become a global language that plays a crucial role in international communication. Vocabulary mastery is one of the fundamental aspects of English learning because it enables students to comprehend texts and communicate effectively in both spoken and written forms. Despite its importance, many junior high school students continue to experience difficulties in acquiring English vocabulary due to conventional and less engaging teaching methods. This study aims to explore the implementation of the Fun English Activity–Pictionary strategy to enhance students’ vocabulary mastery at SMP IT Imam Syafii Cendikia Pekanbaru. A qualitative research approach was employed to examine classroom learning activities and students’ responses throughout the instructional process. The findings indicate that students demonstrated improved vocabulary mastery after participating in Pictionary-based learning activities. The interactive and enjoyable nature of the strategy encouraged active classroom participation and increased students’ motivation to learn English. Therefore, Fun English Activity–Pictionary can be considered an effective instructional strategy for improving vocabulary learning among junior high school students. Keywords : Vocabulary Mastery; Fun English Learning; Pictionary; Game-Based Learning